pH-Metric Studies on Mixed Ligand Complexes of Cd(II)with 2,2´ - Bipyridylamine as Primary Ligand and Diamines as Secondary Ligand - Patel, K.P.; Brahmbhatt, M.P.; Pabreja, D.S.; Joshi, J.D. (Asian Journal of Chemistry, 2010)
The formation of ternary chelates of Cd(II) with 2,2´-bipyridylamine as primary ligand (A) and diamines such as ethylenediamine, 1,2-diaminopropane, 1,3-diaminopropane, N,N-diethyl ethylenediamine, N-N-dimethyl ethylenediamine as secondary ligand (L)has been carried out pH-metrically at 30 ± 0.1°C. The ionic strength was maintained at μ= 0.2 M dm–3. Stability constants have been evaluated and discussed in terms of basicity of ligand, statistical and stereochemical factors.